Complex approach in the treatment and rehabilitation of the patients with myofascial face pain syndrome - I. N. Brega; B. M. Doronin; A. V. Adoniyeva (Бюллетень сибирской медицины)
Determination the tactics of the treatment and rehabilitation of the patients with myofascial face pain syndrome (MFFPS). The complex of clinical and radiologic diagnostic methods to 83 patients with myofascial face pain syndrome and mandible movement disorder have performed. Patient examination have made it possible for to define succession and efforts, to reduce pain syndrome intensity, to normalize mandible movements. MFFPS treatment requires the participation of stomatologist, neurologist, roentgenologist, psychologist, therapeutist.